Effect of combined oral contraceptive on erythropoietin in female waster rats - Toryila, Joseph; K., Amadi; S.O, Odeh; A.B, Adelaiye; A., Mohammed; L N, Achie; U.G., Egesie (International Journal of Biological Research, 2014)
Erythropoietin (EPO), a 30kd glycoprotein is the primary hormonal regulator of erythropoiesis. erythropoietin promotes proliferation and differentiation of erythrocytes progenitor cells leading to production and release of mature reticulocytes expression and haemoglobin synthesis. Erythropoietin may also influence platelet production. This study examined the effort of combined oral contraceptive (COCs) on serum erythropoietin level in female wistar rat. 80 female wistar rats weight 180g – 250g were grouped into four (10 treated and 10 control rats). 0.66g/body weighgt COCs (DUOFEM) was given determined using ELISA kit. There was no significant increased or decreased in serum EPO in the treated groups compared to control groups (p < 0.119). Key word: combined oral contraceptives, erythropoietin, and female wistar rats. Keywords: Combined Oral Contraceptives, Erythropoietin, Female Wistar Rats.